Optimized parameter estimation of a PEMFC model based on improved Grass Fibrous Root Optimization Algorithm - Haibing Guo; Hai Tao; Sinan Q. Salih; Zaher Mundher Yaseen (Energy Reports, 2020)
This paper presents a new optimal methodology for parameter identification of a 50 kW polymer membrane fuel cell (PEMFC) based on the economical-functional model. The objective of the study is to optimal estimation of the system parameters such that the minimum total cost has been needed for the stack construction. The total cost here is the sum of the fuel cell stack cost and its auxiliaries by considering air and hydrogen stoichiometric coefficient, system pressure, the current density, and the system temperature. For solving the minimization problem, a newly modified model of the Grass Fibrous Root Optimization Algorithm (MGRA) has been presented. Final results are compared with some several well-known algorithms to indicate the system efficiency and the reliability of the system toward different parameters has been indicated by applying sensitivity analysis.
Keywords: 330; Electrochemically-mechanically model; Grass Fibrous Root Optimization Algorithm; Parameter identification; Polymer membrane fuel cell; Sensitivity analysis